Enhanced phosphate sequestration by Fe(iii) modified biochar derived from coconut shell. Issue 18 (3rd April 2019) - Zhong, Zhenxing; Yu, Guowen; Mo, Wenting; Zhang, Chunjie; Huang, Hao; Li, Shengui; Gao, Meng; Lu, Xiejuan; Zhang, Beiping; Zhu, Hongping
Abstract : In this work, a novel Fe-modified coconut shell biochar (Fe-CSB) was synthesized and utilized to remove phosphate from aqueous solution. Abstract : In this work, a novel Fe-modified coconut shell biochar (Fe-CSB) was synthesized and utilized to remove phosphate from aqueous solution. Characterization results confirmed that the iron in the Fe(iii )-impregnated CSB existed mainly in the amorphous phase, as ferrihydrite and amorphous hydroxide, which substantially enhanced the phosphate adsorption. Batch experiments indicated that phosphate adsorption on the Fe-CSB was highly dependent on the pH, the humic acid, and temperature, while it was less affected by the nitrate. Phosphate adsorption by the CSB and Fe-CSB could be well described by the pseudo n -th order and Langmuir–Freundlich models. The fitting of the experimental data with the intra-particle diffusion model revealed that surface adsorption and inner-sphere diffusion were involved in the phosphate adsorption process, and that the latter was the rate-controlling step. Batch adsorption experiments and post-adsorption characterization results revealed that the phosphate adsorption by Fe-CSB was primarily governed by four mechanisms: ligand exchange, electrostatic attraction, chemical precipitation, and inner-sphere complexation. This work demonstrated that the modified Fe-CSB is an environmentally friendly and cost-effective bioretention medium and could open up new pathways for the removal of phosphorus from stormwater, as well as solve the problem of waste biomass pollution.